A Review of popular literature during Medieval period - Sheril (Innovative Research Thoughts, 2018)
Medieval literature is a broad subject, encompassing essentially all written works available in Europe and beyond during the middle Ages. that is, the one thousand years from the fall of the Western Roman Empire ca. AD 500 to the beginning of the Renaissance in the 14th, 15th or 16th century, depending on country. The literature of this time was composed of religious writings as well as secular works. Just as in modern literature, it is a complex and rich field of study, from the utterly sacred to the exuberantly profane, touching all points in-between. Works of literature are often grouped by place of origin, language, and genre.